2015
DOI: 10.1007/s13744-015-0322-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Flower Constancy in Bombus atratus Franklin and Bombus bellicosus Smith (Hymenoptera: Apidae) through Palynological Analysis of Nectar and Corbicular Pollen Loads

Abstract: The flower constancy (the visit to a single plant species during a foraging trip) in pollinator insects is a theme widely discussed in behavioral ecology and has an important implication in the evolution of angiosperms. This behavior was studied in the bumblebees Bombus atratus Franklin and Bombus bellicosus Smith through palynological analysis of the nectar and pollen loads of individuals captured while foraging in a restricted area. In both species, there were more individuals with constant flights than with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 31 publications
0
12
1
9
Order By: Relevance
“…(B. transversalis) and Cucurbita spp . (B. morio, B. bellicosus and B. pauloensis ), among others (A.B.E.L.H.A., 2020; Camillo & Garófalo, 1989; Cavalcante, Maués, & Freitas, 2012; Rossi, Santos, & Salvarrey, 2015). Among the studied species, B. morio , B. pauloensis and B. transversalis are classified as of ‘least concern’ by the International Union for Conservation of Nature (IUCN), while there are insufficient data for classification of B. bellicosus , B. brasiliensis and B. brevivillus .…”
Section: Methodsmentioning
confidence: 99%
“…(B. transversalis) and Cucurbita spp . (B. morio, B. bellicosus and B. pauloensis ), among others (A.B.E.L.H.A., 2020; Camillo & Garófalo, 1989; Cavalcante, Maués, & Freitas, 2012; Rossi, Santos, & Salvarrey, 2015). Among the studied species, B. morio , B. pauloensis and B. transversalis are classified as of ‘least concern’ by the International Union for Conservation of Nature (IUCN), while there are insufficient data for classification of B. bellicosus , B. brasiliensis and B. brevivillus .…”
Section: Methodsmentioning
confidence: 99%
“…Why do bee species vary in their degree of flower constancy? Social bees, in particular, are often highly flower constant (Cholis et al, 2020; Free, 1963; Heinrich, 1976, 1979; Hill et al, 1997; Kozuharova, 2018; Pangestika et al, 2017; Rossi et al, 2015; Slaa et al, 2003; White et al, 2001; but see Martínez-Bauer et al, 2021), while flower constancy seems to be less pronounced in solitary bees (Bateman, 1951; Campbell & Motten, 1985; Eckhardt et al, 2014; Jakobsson et al, 2008; Pohl et al, 2011; Smith et al, 2019; Waser, 1986; Williams & Tepedino, 2003). Smith et al (2019), for example, studied pollen composition of 56 bee species and found that individual social bees showed a higher degree of specialisation during a foraging bout than solitary species.…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, se ha reportado la presencia de Bombus terrestris (Linnaeus) en Uruguay como consecuencia de su propagación espontánea luego de su introducción en América con fines comerciales (Dafni et al, 2010). Sin embargo, en los últimos 10 años sólo B. pauloensis y B. bellicosus han sido encontrados en el país (Arbulo et al, 2011(Arbulo et al, , 2015Salvarrey et al, 2013;Rossi et al, 2015). El objetivo de este estudio es constatar las especies de abejorros presentes en Uruguay y su distribución geográfica en el territorio del país.…”
Section: Introductionunclassified